A Statistical Model for Frequency of Coastal Flooding in Honolulu, Hawaii, During the 21st Century. Issue 4 (24th April 2019) - Thompson, Philip R.; Widlansky, Matthew J.; Merrifield, Mark A.; Becker, Janet M.; Marra, John J.
Abstract: The state of Hawaii and city of Honolulu experienced an unprecedented number of minor flooding episodes during 2017 due to the combination of seasonal high tides and record‐high mean sea levels. To quantify the impact of sea level rise on the tendency for flooding events to cluster in future years, we developed a hierarchical statistical model describing the number of days per year for which sea level exceeds a prescribed threshold in Honolulu as a function of annual mean sea level and the amplitude of the highest tides. Based on this model, we generate probabilistic projections of exceedance days per year for the 21st century, which show pronounced inflections in the frequency of exceedance days due to the interaction between sea level rise and long‐period (18.6 year) modulation of tidal amplitude. Analysis of the projections demonstrates how planning for the "typical" future year can substantially underestimate flooding impacts during inevitable severe years that experience many more exceedance days than expected in a probabilistic sense. The projections also show the potential for rapid, subdecadal transitions from occasional to chronic threshold exceedance during the second half of the century, suggesting that implementation of adaptation and mitigation strategies may need to begin prior to the emergence of occasional minor impacts in affected areas. Key Points: The highest sea level events in Honolulu tend to cluster together in time Decadal modulations of tidal amplitude temporarily reduce or enhance impacts of sea level rise Transitions from occasional to chronic threshold exceedance can occur in less than a decade